STRATEGIC IMPERATIVES AND SOCIAL INNOVATIONS IN MANAGING PRODUCT ENVIRONMENTAL PERFORMANCE IN THE CONTEXT OF A CIRCULAR ECONOMY - Шмиголь, Н.М.; Бирський, В.В.; Антонюк, А.А. (Управління змінами та інновації, 2024)
The article demonstrates that the contemporary industrial landscape faces multifaceted environmental and social challenges arising from the increasing waste generation and negative environmental consequences for the population. In response, there is a pressing need to develop robust frameworks to enhance the environmental footprint of production in various industrial sectors. A key direction in addressing these challenges is a paradigm shift towards a circular economy – a model based on reducing waste generation and optimizing resource utilization through principles of reuse and recycling. Within the framework of the circular economy, effective management of the environmental productivity of goods and social innovations takes on paramount importance in order to reduce the negative environmental impacts of enterprises and enhance their resilience. This research is aimed at analyzing the socio-economic nuances of managing environmental productivity in the context of the circular economy and identifying strategic imperatives aimed at fostering sustainable industrial development. The research methodology involved a comprehensive analysis of data from 2016 to 2021, primarily focusing on the processing industry of Ukraine. Based on this analysis, trends and patterns regarding the dynamics of environmental productivity and waste generation in the sector were evaluated. The results underscore the relevance of collective efforts to optimize resource utilization in socio-economic terms and minimize waste generation. Calculation of the comprehensive efficiency index (IE = 1.063) revealed favorable conditions for moderate economic growth in the processing industry during the study period. This growth was accompanied by a reduction in pollution levels of all types, indicating the potential for sustainable development in this sector.